1983
DOI: 10.1037/0033-2909.93.2.232
|View full text |Cite
|
Sign up to set email alerts
|

The frontal eye field and attention.

Abstract: Mammalian sensory systems must continuously select from the ongoing stream of stimulation the events to be noticed, filtering out or habituating to the insignificant. This selective noticing is the province of central mechanisms of orientation and attention that are represented in structures along the neuraxis from brainstem to neocortex. One of those structures is the frontal eye field, long known to be implicated in visual attention through its involvement in horizontal movements of the eyes. In this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(32 citation statements)
references
References 94 publications
2
28
0
1
Order By: Relevance
“…The present study has shown that the major visual-related tha lamic projection to PAGm originates largely from LP. This projection in rats resembles that from the medial subdivision of the pulvinar to the frontal eye fields in monkeys [Bos and Benevento, 1975;Kievit and Kuypers, 1977;Leichnetz, 1982;Crowne, 1983].…”
Section: Discussionmentioning
confidence: 99%
“…The present study has shown that the major visual-related tha lamic projection to PAGm originates largely from LP. This projection in rats resembles that from the medial subdivision of the pulvinar to the frontal eye fields in monkeys [Bos and Benevento, 1975;Kievit and Kuypers, 1977;Leichnetz, 1982;Crowne, 1983].…”
Section: Discussionmentioning
confidence: 99%
“…Human (Neggers et al, 2005) and monkey (Hanes and Wurtz, 2001) research suggests that frontal regions, particularly FEF are also involved in saccade inhibition through the SC. FEF stimulation can produce saccades towards the contralateral side (Blanke et al, 1999) and FEF lesions impair the ability to shift gaze to the contralateral side and can lead to neglect (e.g., Crowne, 1983). Thus frontal responses may be important indicators of both covert and overt attention.…”
Section: Introductionmentioning
confidence: 99%
“…The FEF is not only an important cortical area for planning, programming, and executing eye movements but it is also involved in cognitive mechanisms such as spatial priming, working memory, and memory search (see Vernet et al [4] for a review). Critically, the FEF is also prominently involved in spatial attention (see Crowne [21] for a review), and several studies suggest that both oculomotor and attentional mechanisms are supported by FEF neurons [22][23][24]. Thus, it is plausible that cTBS over the FEF also affected some of these cognitive functions, and this, in turn, contributed to impaired memory recall.…”
Section: Discussionmentioning
confidence: 99%